KNOWLEDGE IMPLEMENTATION IN HEALTH CARE MANAGEMENT: A QUALITATIVE STUDY - Faleh Nafea Alshammari, Saad Hameed Murid Alanazi, Hamad Owayjan Alanazi, Jamal Ahmed S Alsalmi, Hussain Mohammad Ahmed Maashi, Abdulrahman Mohammed Ahmed Hazazi, Farhan Huzaym Hamed Alanazi, Mohammad Aewaijan Alanazi, (Chelonian Research Foundation, 2022)
Knowledge management (KM) is crucial for improving healthcare quality, patient safety, and organizational performance. However, the implementation of KM practices in healthcare settings remains challenging. This study aimed to explore the barriers and facilitators of knowledge implementation in health care management from the perspectives of healthcare professionals in Saudi Arabia. Methods: A qualitative study using semi-structured interviews was conducted with 25 purposively selected healthcare professionals (managers, physicians, nurses, and allied health staff) from three public hospitals in Riyadh, Saudi Arabia. The interviews were audio-recorded, transcribed verbatim, and analyzed using thematic analysis. Results: Four main themes emerged: (1) organizational culture and leadership, (2) communication and collaboration, (3) technology and infrastructure, and (4) individual and team factors. Participants identified several barriers to knowledge implementation, including hierarchical structures, lack of management support, poor communication channels, information silos, inadequate IT systems, time constraints, and resistance to change. Facilitators included supportive leadership, open communication, multidisciplinary teamwork, user-friendly technology, training and education, and individual motivation. Conclusion: Implementing knowledge management in healthcare organizations requires addressing multi-level barriers and leveraging facilitators. Strategies should focus on creating a knowledge-sharing culture, fostering interprofessional collaboration, investing in ICT infrastructure, and building individual and team capacity. The findings provide insights for policymakers, managers, and practitioners to optimize knowledge implementation and improve healthcare performance in Saudi Arabia and beyond. Keywords: Knowledge management, knowledge implementation, healthcare management, qualitative research, Saudi Arabia